E'Ride on!': The Zwift platform as a space for virtual leisure. Issue 2 (4th March 2023) - Reed, Jack; Dunn, Catherine; Beames, Simon; Stonehouse, Paul
ABSTRACT: Virtual environments as spaces for leisure are rapidly emerging within the zeitgeist of 21st century leisure practices. One such environment is the Zwift cycling and running app which provides a series of virtual worlds where cyclists and runners can train, race, and socialise with a global community from their own home. As four authors, we are all in some way curious or engaged with Zwift as a platform for our own leisure. We therefore developed a 'community of inquiry' to provide an initial foray into Zwift as a virtual leisure space. We each produced a section of the paper which focused respectively on assemblage theory, micro-sociology, gender, and morality. Through critique and the spirit of collegiality, these texts were refined and are presented in the paper as separate yet interlinked narratives. Our community of inquiry then reconvened to consider the mechanics of game design and to present Zwift as exhibiting the components of an interreality. The paper concludes with implications for further research which includes considering Zwift as a third space and as a panopticon.